2020
DOI: 10.1186/s12884-020-02940-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between parity and spontaneous preterm birth: a population based study

Abstract: Background Preterm birth is the leading cause of perinatal mortality and neonatal morbidity worldwide. Many factors have been associated with preterm birth, including parity. The aim of the present study was to investigate associations between parity and risk of spontaneous preterm birth. Methods We conducted a retrospective study including live singleton births (≥22 weeks) of women with a first, second, third, fourth or fifth pregnancy in The Netherlands from 2010 through 2014. Our primary outcome was risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
64
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 28 publications
15
64
2
6
Order By: Relevance
“…Our results were consistent with several previous researches [ 15 , 17 , 18 , 21 , 27 ]. For example, a retrospective cohort included 51,086 women from 2002 to 2010 found that the birthweight-for-gestational-age z-score of infants to multiparous mothers was significantly increased compared to nulliparous mothers [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were consistent with several previous researches [ 15 , 17 , 18 , 21 , 27 ]. For example, a retrospective cohort included 51,086 women from 2002 to 2010 found that the birthweight-for-gestational-age z-score of infants to multiparous mothers was significantly increased compared to nulliparous mothers [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…the number of offspring a female has delivered) was also found associated with adverse birth outcomes [ 15 , 16 ]. For example, a recent study with 837,226 singleton births conducted in the Netherlands has found that the risks of PTB, very PTB and extreme PTB were significantly higher in nulliparous mothers than women who had given at least one birth before (RR: 1.95, 95%CI: 1.89–2.00 for PTB; RR: 2.15, 95%CI: 1.98–2.33 for very PTB; and RR: 2.02, 95%CI: 1.78–2.29 for extreme PTB) [ 17 ]. The increased risk of nulliparity on LBW and SGA were also demonstrated in several previous studies [ 15 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We case matched the preterm participants 1:2 with participants who delivered at term (>37 weeks) with a singleton pregnancy. The case matching was performed based on age, parity and gravida [24].…”
Section: Participant Recruitment Clinical History and Sample Collecmentioning
confidence: 99%
“…Prior studies have shown that women with higher pre-pregnancy BMI were more likely to develop pre-eclampsia and diabetes during pregnancy, which greatly increased the risk of PTB 32 . Primiparity is also known to be a risk factor for PTB 33 . Therefore, a logical explanation might be that the existence of strong risk factors for PTB such as obesity might mask the effects of ApoB/ApoA-1 on the occurrence of PTB.…”
Section: Discussionmentioning
confidence: 99%